Effect of a Social Emotional Learning Programme for Primary School Students - Agnes S.K. Wong; Cecilia W.P. Li-Tsang; Andrew M.H. Siu (Hong Kong Journal of Occupational Therapy, 2014)
Objective/Background: This study evaluates the effect of a social emotional learning (SEL) programme for primary school students who have difficulties in social and emotional management, as reported by their teachers or parents. Methods: Twenty-seven primary school students were recruited and randomly assigned to the treatment group (n = 14) and the control group (n = 13). The elementary school version of the Social Skills Rating System was used to assess the social skills and problem behaviours of the participants before and after the programme. The treatment group joined a six-session SEL programme, which was modified and localized based on the Strong Kids Programme. The programme aimed to improve participants' social emotional skills, such as dealing with anxiety and understanding and identifying the emotions of self and others. Each session lasted for about 1 hour and was run in small groups. Results: Problem behaviours were significantly less frequent in the treatment group after the programme (p = .008), but not in the control group. However, no significant changes were found in the measures of social skills. Conclusion: The results of this pilot study show that the SEL can effectively reduce the problem behaviours of primary school students. Implications and future research directions are discussed.